deposition gas

CN122893390APending Publication Date: 2026-10-09DAIKIN INDUSTRIES LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202580018232.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2024-03-01
Filing Date
2025-02-28
Publication Date
2026-10-09

AI Technical Summary

Benefits of technology

[0049]利用本发明,能够提供一种新型的含有氢氟乙烯的沉积气体。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122893390A_ABST
    Figure CN122893390A_ABST
Patent Text Reader

Abstract

It is an object of the present invention to provide a novel deposition gas.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to a deposition gas. Background Technology

[0002] Patent document 1 discloses a plasma treatment gas of a mixture of C4F8 and 2,3,3,3-tetrafluoropropylene.

[0003] Existing technical documents

[0004] Non-patent literature

[0005] Patent Document 1: International Publication No. WO2022 / 074708A1 Summary of the Invention

[0006] The technical problem that the invention aims to solve

[0007] The purpose of this invention is to provide a novel deposition gas containing hydrofluoric acid.

[0008] Technical solutions for solving technical problems

[0009] The present invention comprises the following components.

[0010] Item 1. A deposition gas containing hydrofluoric acid.

[0011] Item 2. The deposition gas as described in Item 1 above, wherein the hydrofluoroethylene is difluoroethylene.

[0012] Item 3. The deposition gas as described in Item 1 above, wherein, in the fabrication of a substrate having a through-silicon electrode (TSV), deposition is used for plasma processing.

[0013] Item 4. The deposition gas as described in Item 1 above, wherein it is used for deposition in the Bosch process during the fabrication of a substrate having a through-silicon electrode (TSV).

[0014] Item 5. A method wherein a substrate for manufacturing a semiconductor is deposited using the deposition gas described in Item 1 above.

[0015] Item 6. The method as described in Item 5 above, wherein,

[0016] The aforementioned substrate is a substrate with a through-silicon electrode (TSV).

[0017] Deposition using the deposition gas of claim 1 for plasma processing.

[0018] Item 7. The method as described in Item 5 above, wherein,

[0019] The aforementioned substrate is a substrate with a through-silicon electrode (TSV).

[0020] In the Bosch process, deposition is performed using the deposition gas described in item 1 above.

[0021] Item 8. A method for depositing on a substrate for manufacturing semiconductors, wherein,

[0022] Using the deposition gas described in item 1 above, the deposition rate (DR) is adjusted under the condition that the following formula is satisfied.

[0023] In use (1) Source power area density (unit: W / cm²) 2 When ) represents the source power density,

[0024] Deposition rate (DR) = -6.8 × 10 14 ×x 2 +1.5×10 9 ×x

[0025] In use (2) Source power volume density (unit: W / cm²) 3 When ) represents the source power density,

[0026] Deposition rate (DR) = -6.6 × 10 19 ×x 2 +4.7×10 11 ×x

[0027] x = (relative intensity of deposited gas) × (square of source power density).

[0028] Relative intensity: This is the relative intensity obtained by using a quadrupole mass spectrometer (QMS) to divide the desired m / z radical intensity by the sum of the mass-to-charge ratio radical intensities of radicals with a mass-to-charge ratio of 1 ≤ m / z ≤ 150 (2.5 times the molecular weight of the deposited gas).

[0029] Free radical strength: (Measured strength for each mass-to-charge ratio (m / z)) × ( ),

[0030] The free radical strength is the measured strength of each mass-to-charge ratio (m / z) multiplied by [the value of the free radical]. This is to correct the quality dependence of the measurement sensitivity of the QMS.

[0031] m: molecular weight

[0032] z: The number of charges generated by ionization within the QMS

[0033] Source power density:

[0034] Source power: Inductively coupled plasma (ICP) power during deposition (unit: W).

[0035] (1) Source power area density (unit: W / cm²) 2 ),

[0036] (2) Source power volume density (unit: W / cm³) 3 ),

[0037] CH2 = relative intensity of CF2 (m / z = 64) × (square of source power density).

[0038] (1) Area of ​​the dielectric window for plasma generation: 2,640 cm² 2 ,

[0039] (2) Volume of the plasma generation region: 46,600 cm³ 3 .

[0040] Item 9. The method as described in Item 8 above, wherein,

[0041] In the above equation x = (relative intensity of the deposited gas) × (square of the source power density),

[0042] The range of x:

[0043] In use (1) Source power area density (unit: W / cm²) 2 When ) represents the source power density, it is 4.0 × 10⁻⁶. -7 ≤x≤2.0×10 -6 ,or

[0044] In use (2) Source power volume density (unit: W / cm²) 3 When ) represents the source power density, it is 1.3 × 10⁻⁶. -9 ≤x≤6.0×10 -9 .

[0045] Item 10. A semiconductor manufacturing apparatus, wherein a gas ejection section for the deposition gas described in Item 1 above is provided.

[0046] Item 11. A method for manufacturing a semiconductor, wherein a substrate for manufacturing a semiconductor is deposited using the deposition gas described in Item 1 above.

[0047] Item 12. The use of the deposition gas described in Item 1 above in semiconductor manufacturing in which a substrate for semiconductor manufacturing is deposited.

[0048] Invention Effects

[0049] Using this invention, a novel deposition gas containing hydrofluoric acid can be provided. Attached Figure Description

[0050] Figure 1This diagram illustrates the evaluation of the etch resistance of deposited films (deposited films). A slow etch rate indicates high etch resistance, meaning the etch resistance is ideal. ■: 1,1-difluoroethylene (CH2=CF2); ◆: c-C4F8.

[0051] Figure 2 This is a graph illustrating the evaluation of the adhesion of the deposited film. (A) For a linewidth of 2 μm and a spacing of 2 μm (3.5 μm resist / Si substrate), plasma treatment was performed on various gases, and the film thickness on the mask surface, sidewalls, and Si surface was measured. (B) is a graph showing the film thickness on the Si surface relative to the sidewalls. Horizontal axis: film thickness on the sidewalls [nm]; Vertical axis: film thickness on the Si surface [nm]; Straight line at slice 0: ●: C3F6; ×: 1,2-difluoroethylene; ▲: 1,1-difluoroethylene; ■: c-C4F8.

[0052] Figure 3 This diagram shows the experimental setup used during TSV processing. The ICP power, process pressure, bias power, and gas flow rate were selected as the experimental setup parameters (variables). Based on these conditions, the experimental setup was used to deposit a protective film onto the Poly-Si film, and data (deposition rate (DR)) was collected.

[0053] Figure 4 This is a graph showing the distribution of deposition rate (DR) calculated using a predictive model to construct a digital twin. The vertical axis represents the deposition rate value, and the horizontal axis represents the gas species. After empirically verifying the virtual experimental results on an actual experimental setup, it was found that alternative gas candidates CHF=CHF and CH2=CF2 have higher deposition rates compared to c-C4F8 and C3F6. The order of maximum deposition rate (DR) is CH2=CF2 > CHF=CFH > C3F6 ≈ c-C4F8. Regarding the maximum DR value, CH2=CF2 and CHF=CFH are superior to c-C4F8.

[0054] Figure 5 This is a graph showing how the apparatus parameters affecting deposition rate (DR) vary depending on the gas type. The parameters affecting DR within the apparatus parameters are ICP power and gas flow rate in FC-based gases, and gas flow rate in HFC-based gases.

[0055] Figure 6This diagram illustrates the film deposition experiment. A Hiden Analytical quadrupole mass spectrometer (QMS) EQP, mounted on the side wall of the experimental setup, was used to measure free radicals (neutral particles) in the CH₂=CF₂ plasma. The QMS measurement was performed in RGA mode, where a positive voltage was applied to prevent positive ions from flowing into the QMS, allowing only neutral particles to be introduced through a 100 μm φ aperture. The amount of ionized particles introduced by collisions with electrons accelerated to 70 eV was measured according to each mass-to-charge ratio (m / z). m represents the mass number of the measured neutral particles, and z represents the charge number of the ionized particles. The following parameters (variables) were selected as experimental setup parameters: ICP power (900W–2700W), process pressure (10mTorr–60mTorr), bias power (0W), gas flow rate (60sccm–175sccm), and electrostatic chuck (ESC, -10℃). Under these conditions, the experimental setup was used to deposit a film on a Poly-Si film, and deposition rate (DR) was collected. Using QMS, free radical measurements were performed in the range of mass-to-charge ratios (m / z) ≤ 1 ≤ 150 (2.5 times the molecular weight of the deposited gas). The measured intensity of each mass-to-charge ratio (m / z) was multiplied by... This is to correct the mass-to-charge ratio dependence of the measurement sensitivity of QMS.

[0056] Figure 7 This is a graph showing the correlation between the horizontal axis (relative intensity of CH2 = CF2 (m / z = 64)) × (square of source power density) and the vertical axis (deposition rate (DR)). Relative intensity is obtained by dividing the desired radical intensity at m / z by the sum of the radical intensities at mass-to-charge ratios of 1 ≤ m / z ≤ 150. Radical intensity is (measured intensity at each mass-to-charge ratio (m / z)) × ( ), that is, multiply the intensity of the measurement of each mass-to-charge ratio (m / z) by The value is obtained by correcting for the mass dependence of QMS measurement sensitivity. Horizontal axis: (relative intensity of CH2 = CF2 (m / z = 64)) × (square of source power density). Vertical axis: deposition rate (DR) [nm / min]. Source power: inductively coupled plasma (ICP) power during deposition. Detailed Implementation

[0057] In this specification, "containing" includes the concepts of "comprise," "consistes substantially of," and "consist of." In this specification, when "A to B" is used to represent a numerical range, it means "above A and below B." In this specification, when parts, %, etc., are used, they represent parts by mass, parts by weight, mass %, or weight % (wt%).

[0058] 1. Deposited gas

[0059] In the miniaturization and high integration technologies of semiconductor devices, three-dimensional integration technologies, represented by chiplets, have attracted attention and are being introduced. A chiplet is a new design approach that divides a large integrated circuit (IC) into multiple small modules, or chips, and then highly integrates and packages them to improve performance. Three-dimensional integration technology increases the integration density of semiconductor devices by stacking transistors and other components vertically.

[0060] A representative 3D integration technology is through-silicon via (TSV) technology, which integrates silicon substrates vertically and is widely used in semiconductor device development. TSV involves creating through-holes (vias) vertically through a silicon substrate, embedding metal to form electrodes, and connecting semiconductor chips. To achieve TSV, etching is required with a width of several μm to tens of μm and a depth of tens to hundreds of μm (deep etching).

[0061] Deep etching is used to etch substrates such as Si with a high aspect ratio.

[0062] Deep etching primarily utilizes a method known as the Bosch process. The Bosch process is a plasma treatment method that sequentially performs the following processes: etching treatment, in which the substrate is etched using plasma with etching gas; deposition treatment, in which a protective film is formed in the recesses created by the above etching treatment using plasma with a protective film forming gas (deposition gas); and treatment that exposes the etched surface through plasma treatment.

[0063] The existing Bosch process uses gases with high global warming potential (GWP) such as c-C4F8 (GWP: 10,300), CF4 (GWP: 7,390), SF6 (GWP: 24,300), CHF3 (GWP: 14,800), and CH2F2 (GWP: 675) in the microfabrication process, which is an environmentally burdensome process.

[0064] In existing Bosch processes, frequent gas switching is required depending on the process, making them a low-productivity process for semiconductor chips. Furthermore, the existing Bosch process can sometimes degrade the electrical properties of semiconductor chips due to the resulting processing shapes (scalloped patterns: sharp, uneven shapes created as etching residue on the etched surface).

[0065] Therefore, a plasma treatment method (Non-Bosch process) that performs etching and deposition simultaneously, different from the Bosch process, was proposed.

[0066] The existing Non-Bosch process also uses c-C4F8 and SF6, gases with high GWP, and is therefore an environmentally demanding process.

[0067] The present invention includes a deposition gas containing hydrofluoric acid for depositing on a substrate for manufacturing semiconductors during semiconductor manufacturing.

[0068] Deposition gas is the gas used for thin film deposition in processes such as chemical vapor deposition (CVD) and physical vapor deposition (PVD) in thin film manufacturing and semiconductor manufacturing.

[0069] hydrofluoroethylene

[0070] The deposition gas of the present invention, using hydrofluoroethylene with low GWP, can effectively deposit semiconductor substrates in both Bosch and Non-Bosch processes.

[0071] In the deposition gas of the present invention, at least one hydrofluoroethylene selected from difluoroethylene and 1,1,2-trifluoroethylene (HFO-1123) is preferably used as hydrofluoroethylene, and difluoroethylene is more preferably used.

[0072] Difluoroethylene includes 1,1-difluoroethylene (HFO-1132a), trans-1,2-difluoroethylene (HFO-1132(E), GWP: 0.0036) and cis-1,2-difluoroethylene (HFO-1132(Z)).

[0073] The deposition gas of the present invention can use one type of hydrofluoroethylene alone, or it can be used by mixing two or more types of hydrofluoroethylene.

[0074] The deposition gas of the present invention contains fluorinated ethylene. Taking the total amount of deposition gas as 100% by volume, from the viewpoint of deposition rate (DR), the deposition gas of the present invention preferably contains 1% to 99% by volume, more preferably 10% to 90% by volume of fluorinated ethylene.

[0075] Other deposited gases

[0076] From the viewpoint of deposition rate (DR) and the tightness in semiconductor device manufacturing, the deposition gas of the present invention may also contain other deposition gases, such as hydrofluorocarbons (HFCs) such as CH2F2, C2H4F2, and C3H2F4; perfluorocarbons (PFCs) such as CF4, C2F6, C3F8, C4F8, C3F6, C4F6, and C5F8; and iodides such as CF3I, C2F5I, and C3F7I.

[0077] The deposition gas of the present invention can be used alone, or two or more of these other deposition gases can be mixed and used.

[0078] Inert gases

[0079] From the viewpoint of deposition rate (DR), the deposition gas of the present invention may also contain an inert gas as needed. Examples of inert gases include one or more rare gases, nitrogen, etc. Examples of rare gases include helium, neon, argon, xenon, krypton, etc., with argon being preferred. These inert gases may be used individually or in combination.

[0080] Deposited gas

[0081] The deposition gas of the present invention exhibits a high deposition rate (DR) for semiconductor substrates.

[0082] The deposition gas of the present invention, by employing the Bosch process in plasma processing, has a high deposition rate (DR) and high film tolerance for substrates such as Si used in semiconductor manufacturing, functions as a thin film, and can be easily removed, thus contributing to improving the productivity of substrates used in semiconductor manufacturing.

[0083] For semiconductor substrates, a protective film is deposited on top of the material being etched during the Bosch process. If the protective film has excessively high etch resistance, it cannot be removed by plasma treatment, and etching cannot proceed.

[0084] The deposition gas of the present invention forms a deposition film exhibiting high film tolerance through deposition (plasma treatment). However, as illustrated in the embodiments of this specification, the protective film formed using the deposition gas of the present invention can be removed under conditions of using etch gas SF6 and applying a bias voltage, and it performs well as a deposition gas for the Bosch process.

[0085] The deposition gas of the present invention is preferably a deposition gas used in plasma processing for manufacturing substrates having through-silicon electrodes (TSVs). The plasma processing of the present invention includes Bosch processes and Non-Bosch processes.

[0086] The deposition gas of the present invention is more preferably the deposition gas used in the Bosch process for deposition in the manufacture of substrates having through-silicon electrodes (TSVs).

[0087] In the fabrication of a substrate with a through-silicon electrode (TSV), the Bosch process is employed, and during its deposition (process), the substrate can be well etched at a high aspect ratio (deep etching) by using the deposition gas of the present invention.

[0088] The deposition gas of this invention is a low-GWP gas, and using the Bosch process, it enables a low-environmental-impact and continuous microfabrication technology for semiconductor manufacturing substrates.

[0089] 2. Deposition methods

[0090] The present invention includes a method for depositing a substrate for manufacturing semiconductors using a deposition gas containing hydrofluoroethylene (preferably difluoroethylene) as a gas supplied for generating plasma.

[0091] The deposition method of the present invention is preferably a method for deposition using the deposition gas of the present invention in plasma processing on a substrate having a through-silicon electrode (TSV) as a substrate for semiconductor manufacturing. The plasma processing of the present invention includes Bosch processes and Non-Bosch processes.

[0092] The deposition method of the present invention is more preferably a method of deposition using the deposition gas of the present invention, performed in plasma processing on a substrate having a through-silicon electrode (TSV) as a substrate for semiconductor manufacturing.

[0093] In the fabrication of a substrate with a through-silicon electrode (TSV), plasma processing preferably employs the Bosch process, in which the substrate can be well etched at a high aspect ratio (deep etching) by using the deposition gas of the present invention during its deposition process.

[0094] The present invention includes a method for depositing a semiconductor substrate by adjusting the deposition rate (DR) using a deposition gas containing hydrofluoroethylene (preferably difluoroethylene) as a gas supplied for generating plasma.

[0095] Free radicals in plasma generated from deposited gases (CH2=CF2, etc.) were measured using a quadrupole mass spectrometer (QMS).

[0096] QMS measurement conditions at this time:

[0097] Measurement mode: RGA mode (prevents positive ion inflow)

[0098] Hole size: 100μmφ

[0099] The energy of an electron that ionizes a neutral particle: 70 eV

[0100] Measurement range for mass-to-charge ratio: 1 ≤ m / z ≤ 150

[0101] Experimental apparatus parameters (variables)

[0102] Inductively Coupled Plasma (ICP) Power: 900W~2700W

[0103] Process pressure: 10mTorr~60mTorr

[0104] Bias power: 0W

[0105] Gas flow rate: 60 sccm~175 sccm

[0106] Electrostatic chuck (ESC): -10℃

[0107] Select the experimental setup parameters, and use the experimental setup under these conditions to deposit the film onto the Poly-Si film, and collect the deposition rate (DR).

[0108] The free radical intensities with mass-to-charge ratios within a range of 2.5 times the molecular weight of the deposited gas (CH2=CF2, etc.) (1≤m / z≤150 for CH2=CF2) were determined, and each intensity was multiplied by... (m: mass number of each neutral particle). By multiplying each intensity by This is to correct the quality dependence of the measurement sensitivity of QMS.

[0109] The relative strength is calculated by dividing the desired m / z radical strength by the sum of the radical strengths of free radicals with a mass-to-charge ratio of 1 ≤ m / z ≤ 150.

[0110] The free radical strength is (the measured strength of each mass-to-charge ratio (m / z)) × ( ), that is, multiply the intensity of each mass-to-charge ratio (m / z) by To correct the quality dependence of QMS measurement sensitivity.

[0111] The free radical intensity of the deposition gas can be appropriately adjusted under free radical generation conditions such as the temperature of the semiconductor substrate used for deposition and the experimental device parameters (ICP power, process pressure, bias power, gas flow rate, ESC, etc.).

[0112] The deposition method of the present invention, for semiconductor manufacturing substrates, uses the deposition gas of the present invention and adjusts the deposition rate (DR) under the condition that the following formula is satisfied, to perform deposition.

[0113] In use (1) source power area density (unit: W / cm²) 2 When ) represents the source power density,

[0114] Deposition rate (DR) = -6.8 × 10 14 ×x 2 +1.5×10 9 ×x

[0115] In use (2) Source power volume density (unit: W / cm²) 3 When ) represents the source power density,

[0116] Deposition rate (DR) = -6.6 × 10 19 ×x 2 +4.7×10 11 ×x

[0117] x = (relative intensity of deposited gas) × (square of source power density)

[0118] Relative intensity: This is the relative intensity obtained by using a quadrupole mass spectrometer (QMS) to divide the measured radical intensity of the deposited gas at the desired m / z by the sum of the radical intensities of free radicals with a mass-to-charge ratio of 1 ≤ m / z ≤ 150 (2.5 times the molecular weight of the deposited gas).

[0119] Free radical strength: (Measured strength for each mass-to-charge ratio (m / z)) × ( )

[0120] The free radical strength is the measured strength of each mass-to-charge ratio (m / z) multiplied by [the value of the free radical]. This is to correct the quality dependence of the measurement sensitivity of the QMS.

[0121] m: molecular weight

[0122] z: The number of charges generated by ionization within the QMS

[0123] Source power density:

[0124] Source power: Inductively coupled plasma (ICP) power during deposition (unit: W)

[0125] (1) Source power area density (unit: W / cm²) 2 )

[0126] (2) Source power volume density (unit: W / cm³) 3 )

[0127] The relative intensity of CH2 = CF2 (m / z = 64) × (the square of the source power density)

[0128] (1) Area of ​​the dielectric window for plasma generation: 2,640 cm² 2

[0129] (2) Volume of the plasma generation region: 46,600 cm³ 3

[0130] In the deposition method, the deposition rate (DR) is preferably 500 nm / min or higher.

[0131] In the above x = (relative intensity of deposited gas) × (square of source power density), using (1) source power area density (unit: W / cm²) 2 When x represents the source power density, the preferred range of x is 4.0 × 10⁻⁶. -7 ~2.0×10 -6 .

[0132] 4.0×10 -7 ≤x≤2.0×10 -6

[0133] In the above x = (relative intensity of deposited gas) × (square of source power density), using (2) source power volume density (unit: W / cm³) 3 When x represents the source power density, the preferred range of x is 1.3 × 10⁻⁶. -9 ~6.0×10 -9 .

[0134] 1.3×10 -9 ≤x≤6.0×10 -9

[0135] The ICP power is preferably adjusted within the range of 900W to 2700W.

[0136] 3. Semiconductor manufacturing equipment

[0137] The present invention includes a semiconductor manufacturing apparatus having a gas ejection section containing a deposition gas containing hydrofluoroethylene.

[0138] 4. Semiconductor manufacturing methods

[0139] The present invention includes a method for manufacturing a semiconductor by depositing a substrate for semiconductor manufacturing using a deposition gas containing hydrofluoric acid according to the present invention.

[0140] 5. Uses in semiconductor manufacturing

[0141] The present invention includes the use of the deposition gas containing hydrofluoric acid of the present invention in semiconductor manufacturing in which a substrate for semiconductor manufacturing is deposited.

[0142] The deposition gas of the present invention is preferably applicable to the Bosch process, which involves sequentially repeating the following steps: an etching process in which a substrate is etched using plasma of an etching gas; a deposition process in which a protective film is formed in the recesses formed by the etching process using plasma of the deposition gas of the present invention; and a process in which the etched surface is exposed by plasma treatment. The deposition gas of the present invention exhibits good deposition rate (DR) for substrates such as Si used in semiconductor manufacturing, which helps to improve the productivity of substrates used in semiconductor manufacturing.

[0143] The embodiments of the present invention have been described above. Various changes can be made to the methods and details without departing from the spirit and scope of the claims of the present invention.

[0144] Example

[0145] The present invention will now be specifically described using examples and comparative examples. However, the present invention is not limited to these examples.

[0146] Plasma processing methods of the embodiments and comparative examples

[0147] (1) Deposition rate (DR)

[0148] The source power dependence of deposition rate (DR), one of the important properties of deposition gas, is evaluated.

[0149] Deposition (preparation of deposited films)

[0150] In an ICP (Inductively Coupled Plasma) device, under deposition conditions of 20 sccm gas flow rate, 10 mTorr pressure, 0 W bias voltage, and 100 W, 200 W, and 300 W source power, silicon substrates (Si) and silicon oxide films (SiO2, TEOS) formed on the silicon substrates were deposited (Table 1).

[0151] Deposited gas: 1,2-difluoroethylene (CHF=CHF)

[0152] Deposited gas: Octafluorocyclobutane (c-C4F8)

[0153] [Table 1]

[0154]

[0155] In the examples (CHF=CHF), deposition was confirmed, and the DR was larger compared to the comparative example (c-C4F8). The deposition gas of the present invention contains hydrofluoroethylene, which can be expected to shorten the deposition process time in plasma processing methods, and is therefore useful as a deposition gas.

[0156] (2) Splash resistance

[0157] By using Ar-sputtering with XPS (X-ray Photoelectron Spectroscopy), the sputtering velocity of the deposited film in a structure consisting of a deposited film (deposited gas: CHF=CHF or c-C4F8) / polycrystalline silicon film (PolySi) / silicon oxide film (SiO2) / silicon substrate (Si) is derived, and the robustness (sputtering resistance) of the film is evaluated.

[0158] Deposition (preparation of deposited films)

[0159] Deposition was performed on a silicon substrate (Si) and a silicon oxide film (SiO2) formed on the silicon substrate under the following deposition conditions: ICP device, gas flow rate 70 sccm, pressure 5 mTorr, bias voltage 0 W, and source power 200 W.

[0160] Sputtering

[0161] In the example (deposited film using deposition gas CHF=CHF), the deposited film was barely removed even after prolonged sputtering. In the comparative example (deposited film using deposition gas c-C4F8), the deposited film was removed.

[0162] In the example (CHF=CHF), the deposited film is hard compared to the comparative example (c-C4F8) in Ar-GCIB (Gas Cluster Ion Beam) sputtering (5kV, 20nA). The deposition gas of the present invention contains hydrofluoroethylene, which enables the preparation of a sputter-resistant deposited film in a plasma processing method.

[0163] (3) Etching resistance

[0164] Film fabrication of deposited membranes (deposited membranes)

[0165] Deposited films were fabricated by varying the apparatus parameters (ICP power, system pressure, bias power, and gas flow rate) according to the conditions in Table 2 below. The tolerance of the deposited film with contact holes (2 μm diameter) patterned on a 0.5 μm TEOS mask / Si substrate and deposited on the top (TEOS top) was evaluated.

[0166] [Table 2]

[0167]

[0168] Etch resistance of deposited film

[0169] The deposited film was etched with SF6 using an ICP device (processing time: 35s (C2H2F2), 60s (c-C4F8), Esc temperature: 20℃). The etching rate of the deposited film was calculated by using the difference between the film thickness at the time of deposition and the film thickness after etching (Table 3).

[0170] [Table 3]

[0171]

[0172] Figure 1 This is a diagram illustrating the evaluation of the etch resistance of a deposited film (accumulated film). A slow etch rate of the deposited film indicates high etch resistance, suggesting that the etch resistance is ideal.

[0173] ■:1,1-Difluoroethylene (CH2=CF2)

[0174] ◆:c-C4F8

[0175] In Example (CH2=CF2) (■), compared with Comparative Example (c-C4F8) (◆), the etching rate (ER) was lower, the disappearance of the deposited film was suppressed, and good etching resistance was observed (Table 3 and Figure 1 The deposition gas of this invention contains hydrofluoroethylene, which, in a plasma processing method, enables the preparation of a deposition film with good etch resistance.

[0176] (4) Evaluation of adhesion

[0177] The adhesion of the deposited film was evaluated. As an evaluation of adhesion, in the Si deep cutting process (Bosch process), the deposited film adhered to the sidewalls but was difficult to adhere to the bottom surface, indicating that the Si deep cutting process was excellent.

[0178] Figure 2 This is a diagram illustrating the evaluation of the adhesion of the deposited film.

[0179] (A) Under the conditions of 2μm linewidth and 2μm spacing (3.5μm resist / Si substrate), plasma treatment was performed on each gas, and the film thickness of the mask surface, sidewalls and Si surface was measured.

[0180] (B) Calculation of approximate curves

[0181] This is a graph showing the film thickness of the Si surface relative to the sidewalls.

[0182] Horizontal axis: Film thickness on the sidewalls [nm]

[0183] Vertical axis: Film thickness on the Si surface [nm]

[0184] The line of slice 0

[0185] ●:C3F6

[0186] ×:1,2﹣Difluoroethylene

[0187] ▲: 1,1-Difluoroethylene

[0188] ■:c-C4F8

[0189] After calculating approximate curves (linear) based on the data points of each gas, the deposited films formed using 1,2-difluoroethylene (×) or 1,1-difluoroethylene (▲) show a smaller slope compared to the deposited films formed using c-C4F8 (■) or C3F6 (●).

[0190] Compared to the sidewalls, gases are more difficult to deposit on the Si surface (bottom).

[0191] According to the approximate curve ( Figure 2 In c-C4F8 (■), if a film thickness of 100 nm is formed on the sidewalls (horizontal axis), then a film thickness of approximately 190 nm will be formed on the bottom surface (Si surface) (vertical axis). On the other hand, in CH2=CF2 (▲), if a film thickness of 100 nm is formed on the sidewalls (horizontal axis), then a film thickness of approximately 110 nm will be formed on the bottom surface (Si surface) (vertical axis). CH2=CF2 (▲) can form a deposition film that is difficult to adhere to the bottom surface (Si surface) (it adheres to the bottom surface (Si surface) very thinly).

[0192] 1,2-difluoroethylene, 1,1-difluoroethylene, and other hydrofluoroethylenes are gases that are difficult to deposit on the Si surface (bottom surface) relative to the sidewalls. Figure 2 (Table 4). In the Si deep drilling process (Bosch process) that protects the sidewalls and etches Si, excellent deposition films for the formation of hydrofluoroethylene can be evaluated.

[0193] [Table 4]

[0194]

[0195] Typically, in Si deep drilling (Bosch process), it is desirable for the deposited film to adhere thinly to the bottom surface of the recess formed by etching. This invention forms a deposited film using a deposition gas containing hydrofluoroethylene such as 1,2-difluoroethylene and 1,1-difluoroethylene. Compared to deposited films formed using c-C4F8 or C3F6, the deposited film adheres thinly to the bottom surface of the recess formed by etching, which is particularly superior in Si deep drilling (Bosch process).

[0196] (5) Development of high-efficiency TSV using digital twins with low GWP gas

[0197] Figure 3 This diagram shows the experimental setup used during TSV processing. The experimental setup parameters (variables) were selected, a protective film was deposited on the Poly-Si film, and data (deposition rate (DR)) was collected.

[0198] Exploring high-efficiency TSVs using low-GWP gases. A digital twin is a virtual (although virtual, it is an alternative reality with the same effect as the real one) object, system, or process reproduced on a computer.

[0199] The process of gas exploration using digital twins is characterized by conducting comprehensive virtual experiments on digital twins through "predictive models" built on highly efficient experiments.

[0200] First, from a chemical perspective, alternative gas candidates that outperform existing c-C4F8 in terms of deposition rate, a performance indicator of deposition gases, were explored. As a result, C3F6, CHF=CHF, and CH2=CF2, with a GWP less than 1, were selected as alternative gas candidates.

[0201] Next, to obtain the optimal parameter settings with fewer experiments, the experimental design method was used. The experimental design method, belonging to the applied field of mathematical statistics, is a method for studying efficient experimental planning and analysis by examining whether specific factors have an effect on a subject. Therefore, 19 conditions were selected as the device parameters (variables) for the actual experiment: ICP power, process pressure, bias power, and gas flow rate. The actual experiment was conducted based on these conditions.

[0202] The experimental setup used was the same model as the setup used in mass production for TSV processing. Figure 3 This allows a protective film to be deposited on the Poly-Si film, enabling the collection of data (deposition rate (DR)).

[0203] Next, based on the experimental results, a "prediction model" was constructed to predict the deposition rate (DR) based on device parameters. Using this prediction model, a digital twin that reproduces the actual process conditions was built, and 490 virtual experiments were conducted in digital space to calculate the distribution of the deposition rate (DR).

[0204] Figure 4 It is a graph that uses a predictive model to build a digital twin and calculates the distribution of deposition rate (DR).

[0205] exist Figure 4 In the diagram, the vertical axis represents the deposition rate, and the horizontal axis represents the gas species. After empirically verifying the results of this virtual experiment in an actual experimental setup, it was found that the alternative gas candidates CHF=CHF and CH2=CF2 exhibited higher deposition rates compared to c-C4F8 and C3F6. Figure 4 ).

[0206] Typically, the exploration of alternative gases employs a local optimum approach, exploring the conditions surrounding the reference gas (currently c-C4F8 used as the deposition gas). By using digital twins, gas exploration can be conducted within a broader condition space, thus enabling the determination of the overall optimum and reducing experimental time from 245 hours to approximately 30 minutes.

[0207] The order of maximum deposition rate (DR) is CH2=CF2>CHF=CFH>C3F6≈c-C4F8. Regarding the maximum DR, CH2=CF2 and CHF=CFH are superior to c-C4F8 and C3F6. Figure 4 ).

[0208] Figure 5 This is a graph showing how the device parameters affecting the deposition rate (DR) vary depending on the type of gas.

[0209] It has been clarified that the device parameters affecting the deposition rate (DR) vary depending on the type of gas. Figure 5 In FC-based gases (c-C4F8 and C3F6), it was determined that ICP power and gas flow rate within the apparatus parameters can affect deposition rate (DR). In HFC-based gases (CHF=CHF and CH2=CF2), it was determined that gas flow rate within the apparatus parameters can affect deposition rate (DR). Using digital twin technology, it is possible to explore high-efficiency TSV using low-GWP gases (with reduced environmental impact).

[0210] (6) Development of sedimentation methods for adjusting deposition rate (DR)

[0211] Figure 6 This is a diagram showing a film-forming experiment for depositing a film.

[0212] The free radicals of the deposited gas (CH2=CF2) in the plasma were measured using a quadrupole mass spectrometer (QMS), and the ion density was determined.

[0213] QMS measurement conditions at this time:

[0214] Measurement mode: RGA mode (prevents positive ion inflow)

[0215] Hole size: 100μmφ

[0216] The energy of an electron that ionizes a neutral particle: 70 eV

[0217] Measurement range for mass-to-charge ratio: 1 ≤ m / z ≤ 150

[0218] Select the experimental setup parameters (variables), and use the experimental setup under these conditions to deposit the film onto the Poly-Si film, collecting the deposition rate (DR).

[0219] Experimental apparatus parameters (variables)

[0220] ICP power: 900W~2700W

[0221] Process pressure: 10mTorr~60mTorr

[0222] Bias power: 0W

[0223] Gas flow rate: 60 sccm~175 sccm

[0224] Electrostatic chuck (ESC): -10℃

[0225] The free radical intensities with mass-to-charge ratios within a range of 2.5 times the molecular weight of the deposited gas (CH2=CF2, etc.) (for CH2=CF2, 1≤m / z≤150) were determined, and each intensity was multiplied by... (m: molecular weight). By multiplying each intensity by This corrected the quality dependence of the measurement sensitivity of QMS.

[0226] The relative strength is calculated by dividing the desired m / z radical strength of the deposited gas by the sum of the radical strengths of the mass-to-charge ratios of 1 ≤ m / z ≤ 150.

[0227] Free radical strength is calculated by multiplying (the measured strength of each mass-to-charge ratio (m / z)) by ( ), that is, multiply the intensity of the measurement of each mass-to-charge ratio (m / z) by This corrected the quality dependence of QMS measurement sensitivity.

[0228] The free radical intensity of the deposition gas was appropriately adjusted under the conditions of free radical generation, such as the temperature of the semiconductor substrate used for deposition and the experimental device parameters (ICP power, process pressure, bias power, gas flow rate, ESC, etc.).

[0229] like Figure 6 As shown, a quadrupole mass spectrometer (QMS) EQP manufactured by Hiden Analytical, mounted on the side wall of the experimental setup, was used to measure free radicals (neutral particles) in the CH2=CF2 plasma. The QMS measurement was performed in RGA mode, where a positive voltage was applied to prevent positive ions from flowing into the QMS, allowing only neutral particles to be introduced through a 100 μm φ pore.

[0230] Neutral particles introduced by collisions with electrons accelerated to 70 eV are ionized according to each mass-to-charge ratio (m / z). m represents the molecular weight of the neutral particle measured. z represents the charge number of the particle ionized (ionized) within the QMS.

[0231] Using QMS, free radical measurements were performed in the range of mass-to-charge ratios (m / z) ≤ 1 ≤ m / z ≤ 150 (2.5 times the molecular weight of the deposited gas). The measured intensity of each mass-to-charge ratio (m / z) was multiplied by... This corrects the mass-to-charge ratio dependence of the measurement sensitivity of QMS.

[0232] Figure 7 This is a graph showing the correlation between the horizontal axis (relative intensity of CH2 = CF2 (m / z = 64)) × (square of source power density) and the vertical axis (deposition rate (DR)).

[0233] The relative strength is the relative strength obtained by dividing the desired m / z free radical strength by the sum of the mass-to-charge ratios of free radicals with a mass-to-charge ratio of 1 ≤ m / z ≤ 150.

[0234] Free radical strength is the measured strength of each mass-to-charge ratio (m / z) × ( ), that is, multiply the intensity of the measurement of each mass-to-charge ratio (m / z) by The value was corrected for the quality dependence of QMS measurement sensitivity.

[0235] Horizontal axis: (relative intensity of CH2 = CF2 (m / z = 64)) × (square of source power density)

[0236] Vertical axis: Deposition rate (DR) [nm / min]

[0237] Source power: Inductively coupled plasma (ICP) power during deposition.

[0238] [Table 5]

[0239]

[0240] [Table 6]

[0241]

[0242] Based on experimental results, in the method of depositing on a substrate for semiconductor manufacturing, the deposition rate (DR) can be adjusted by using a deposition gas under the condition that the following formula is satisfied.

[0243] In use (1) source power area density (unit: W / cm²) 2 When ) represents the source power density,

[0244] Deposition rate (DR) = -6.8 × 10 14 ×x 2 +1.5×10 9 ×x

[0245] In use (2) Source power volume density (unit: W / cm²) 3 When ) represents the source power density,

[0246] Deposition rate (DR) = -6.6 × 10 19 ×x 2 +4.7×10 11 ×x

[0247] x = (relative intensity of deposited gas) × (square of source power density)

[0248] Relative intensity: It is the relative intensity obtained by multiplying the desired m / z free radical intensity by the sum of the mass-to-charge ratio free radical intensities of 1 ≤ m / z ≤ 150 (2.5 times the molecular weight of the deposited gas) using a quadrupole mass spectrometer (QMS).

[0249] Free radical strength: (Measured strength for each mass-to-charge ratio (m / z)) × ( )

[0250] The free radical strength is the measured strength of each mass-to-charge ratio (m / z) multiplied by [the value of the free radical]. This is to correct the quality dependence of the measurement sensitivity of the QMS.

[0251] m: molecular weight

[0252] z: The number of charges generated by ionization within the QMS

[0253] Source power density:

[0254] Source power: Inductively coupled plasma (ICP) power during deposition (unit: W)

[0255] (1) Source power area density (unit: W / cm²) 2 )

[0256] (2) Source power volume density (unit: W / cm³) 3 )

[0257] The relative intensity of CH2 = CF2 (m / z = 64) × (the square of the source power density)

[0258] (1) Area of ​​the dielectric window for plasma generation: 2,640 cm² 2

[0259] (2) Volume of the plasma generation region: 46,600 cm³ 3

[0260] In the deposition method, the deposition rate (DR) is preferably 500 nm / min or higher.

[0261] Based on the experimental results, when x = (relative intensity of deposited gas) × (square of source power density), when using (1) source power area density (unit: W / cm²), 2 When x represents the source power density, the range of x is 4.0 × 10⁻⁶. -7 ~2.0×10 -6 .

[0262] 4.0×10 -7 ≤x≤2.0×10 -6

[0263] Based on the experimental results, when x = (relative intensity of deposited gas) × (square of source power density), the source power volume density (unit: W / cm³) is used in (2) 3 When x represents the source power density, the range of x is 1.3 × 10⁻⁶. -9 ~6.0×10 -9 .

[0264] 1.3×10 -9 ≤x≤6.0×10 -9

[0265] This invention provides a novel deposition gas for TSV processing with low environmental impact (low GWP gas for high-efficiency TSV). With the widespread adoption of three-dimensional integration technology, its introduction will be significant, thereby making a substantial contribution to reducing environmental impact. This invention provides a gas oriented towards miniaturization and high integration, and offers an environmentally friendly gas that reduces environmental impact and efficiently utilizes energy.

Claims

1. A deposition gas, characterized in that: It contains hydrofluoric acid.

2. The deposition gas as described in claim 1, characterized in that: The hydrofluoroethylene is difluoroethylene.

3. The deposition gas as described in claim 1, characterized in that: In the fabrication of a substrate with a through-silicon electrode (TSV), deposition is used for plasma processing.

4. The deposition gas as described in claim 1, characterized in that: Deposition for Bosch process in the fabrication of substrates with through-silicon electrodes (TSVs).

5. A method, characterized in that: The substrate for manufacturing semiconductors is deposited using the deposition gas described in claim 1.

6. The method as described in claim 5, characterized in that: The substrate is a substrate with a through-silicon electrode (TSV). Deposition using the deposition gas of claim 1 for plasma processing.

7. The method as described in claim 5, characterized in that: The substrate is a substrate with a through-silicon electrode (TSV). In the Bosch process, deposition is performed using the deposition gas described in claim 1.

8. A method for depositing on a substrate for manufacturing semiconductors, characterized in that: Using the deposition gas of claim 1, the deposition rate (DR) is adjusted under the condition that the following formula is satisfied. In use (1) Source power area density (unit: W / cm²) 2 When ) represents the source power density, Deposition rate (DR) = -6.8 × 10 14 ×x 2 +1.5×10 9 ×x In use (2) Source power volume density (unit: W / cm²) 3 When ) represents the source power density, Deposition rate (DR) = -6.6 × 10 19 ×x 2 +4.7×10 11 ×x x = (relative intensity of deposited gas) × (square of source power density). Relative intensity: This is the relative intensity obtained by dividing the desired m / z radical intensity measured using a quadrupole mass spectrometer (QMS) by the sum of the mass-to-charge ratio radical intensities of radicals with a mass ratio of 1 ≤ m / z ≤ 150 (2.5 times the molecular weight of the deposited gas). Free radical strength: (Measured strength for each mass-to-charge ratio (m / z)) × ( ), The free radical strength is the measured strength of each mass-to-charge ratio (m / z) multiplied by [the value of the free radical]. This is to correct the quality dependence of the measurement sensitivity of the QMS. m: molecular weight z: The number of charges generated by ionization within the QMS Source power density: Source power: Inductively coupled plasma (ICP) power during deposition (unit: W). (1) Source power area density (unit: W / cm²) 2 ), (2) Source power volume density (unit: W / cm³) 3 ), CH2 = relative intensity of CF2 (m / z = 64) × (square of source power density). (1) Area of ​​the dielectric window for plasma generation: 2,640 cm² 2 , (2) Volume of the plasma generation region: 46,600 cm³ 3 .

9. The method as described in claim 8, characterized in that: In the given x = (relative intensity of the deposited gas) × (square of the source power density), The range of x: In use (1) Source power area density (unit: W / cm²) 2 When ) represents the source power density, it is 4.0 × 10⁻⁶. -7 ≤x≤2.0×10 -6 ,or In use (2) Source power volume density (unit: W / cm²) 3 When ) represents the source power density, it is 1.3 × 10⁻⁶. -9 ≤x≤6.0×10 -9 .

10. A semiconductor manufacturing apparatus, characterized in that: A gas ejection section having the deposited gas as described in claim 1.

11. A method for manufacturing a semiconductor, characterized in that: The deposition gas described in claim 1 is used to deposit a substrate for manufacturing semiconductors.

12. Use of the deposition gas of claim 1 in semiconductor manufacturing in which a substrate for semiconductor manufacturing is deposited.

Citation Information

Patent Citations

  • Plasma processing gas, plasma processing method, and plasma processing apparatus

    WO2022074708A1